Two Transgender Men Receiving Subdermal Testosterone Pellets for Gender Affirmation - Sune L. Wolf Pulsiano, M3; Jenna L. Sarvaideo, DO (AACE Clinical Case Reports, 2023)
Background/Objective: Testosterone treatment is employed in transgender men to help them affirm their gender. Our objective is to report the cases of 2 transgender men who received subdermal testosterone pellets as the mode of testosterone administration. Case Report: Both patients presented for discussion of testosterone therapy. Patient 1 was a 47-year-old transgender male. He had bilateral mastectomy and total abdominal hysterectomy with bilateral salpingo-oophorectomy (TAH-BSO). Physical exam was significant for obesity. He was on injectable testosterone for 9 years and experienced voice deepening, facial hair growth, temporal hair thinning, and increased skin oiliness, but was interested in a long-acting testosterone formulation. Pellets were well tolerated, but the patient ultimately chose to return to injections. Patient 2 was a 20-year-old transgender male with no history of gender-affirming surgeries. Physical exam was pertinent for a thin, masculinized individual. He started on testosterone gel, but switched to weekly injections, on which he experienced voice deepening, increased skin oiliness and cessation of menses. Due to pain with injections and desire for a long-acting formulation, he elected to try pellets. Discussion: The dose of testosterone pellets used in transgender men are similar to those employed for testosterone replacement in hypogonadal cisgender men. Conclusion: Subdermal testosterone pellets may be suitable as a means of delivering testosterone in transgender men, but the 2 cases reported here do not permit firm conclusions. Given the widespread use of testosterone for gender affirmation in transgender men, a prospective controlled study of subdermal testosterone pellets seems indicated.